Effect of Pomegranate Juice and Sildenafil on Intrauterine Growth Retardation: A Randomized Controlled Trial - Khadijeh Nasri; Fatemeh Ghaedi; Fatemeh Safi; SeyedAmirhossein Latifi; Amir Almasi-Hashiani (International Journal of Fertility and Sterility)
Background: There is evidence that pomegranate juice and sildenafil can be effective supplements especially in pregnancy. Therefore; this study aimed to compare the effect of pomegranate juice and sildenafil on Doppler ultrasound findings, Apgar score and fetal estimated weight (FEW) in cases with intrauterine growth retardation (IUGR).Materials and Methods: This randomized clinical trial conducted on a population of naturally pregnant women with IUGR in Arak city (Arak, Iran) during October 2021 to January 2022. Participants were randomly divided into two equal groups (n=27) that received pomegranate juice (230 ml daily dose for 6 weeks, Narnoosh, Arak, Iran) and sildenafil (25 mg, three times a day for 6 weeks, Marham Daru Co., Tehran, Iran). Doppler ultrasound evaluation, including umbilical artery pulsatility index (PI), uterine artery PI and FEW were assessed by a gynecologic resident along with a radiologist immediately after intervention, and birth weight and 1- and 5-minute Apgar scores were registered by a neonatologist.Results: Twenty-one cases in pomegranate juice group and 23 cases in sildenafil group were included in the analysis. The mean age and weight of participants were 27.1 ± 4.7 year and 68.5 ± 11.5 kg, respectively. The results showed that there was no significant difference between the two groups in terms of mean Apgar score of 1 minute (P=0.631), 5 minutes (P=0.323) and birth weight (P=0.580). No significant difference was observed between two groups in terms of uterine artery PI (P=0.301) and umbilical artery PI (P=0.168), but the EFW changes in the sildenafil group were significantly greater than the pomegranate group (P=0.009).Conclusion: The results of our study showed that pomegranate juice has a similar effect of sildenafil in IUGR. Therefore, it is recommended to design more studies to achieve results that are more valid (registration number: IRCT20210730052014N1).